Communication and information technologies annual : politics, participation, and production - Robinson, Laura (Sociologist); Cotten, Shelia R.; Schulz, Jeremy (Studies in media and communications, 2015)
This volume brings together nine studies of the digital public sphere. The contributions illuminate three key areas of digital citizenship, namely political engagement, participation networks, and content production. As a whole, the contributions revisit old questions and answer important new queries about netizenship and the digital public sphere.